The Impact of Innovation Strategies on Competitive Advantage: The Role of Students in the Digital Creative Industry during Industry 5.0 - Hajar Dewantara; Muhammad Hafish; Muhammad Aldi Pranata; Ulfa Fitriah R (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2024)
The purpose of this study is to analyze the impact of innovative strategies on the competitiveness of creative industry businesses in the Industry 5.0 era. This study aims to analyze the impact of innovative strategies on the competitiveness of creative industry businesses in the Industry 5.0 era, as well as explore the role of students in supporting innovation in the sector. The role of teachers in encouraging innovation in a particular sector. The analysis method used is a quantitative descriptive approach with data collection. The analysis method used is a quantitative descriptive approach with data collection. through a survey of students working in the digital creative industry. The results showed that innovation strategies, including new product/service development, process innovation, and function modification, have a significant influence in creating sustainable competitive advantages for companies. Students, as a young generation who are educated and familiar with technology, have great potential to contribute to innovation in the digital creative industry through fresh mindsets, openness to new ideas, and responsiveness to change.